Security considerations for smartphone devices - Almina Mušinbegović; Harun Alijagic; Amer Hrnjic; Ali Abd Almisreb (Defense and Security Studies)
In the paper the ways in which smartphone devices are designed to be secure are investigated. Different approaches were examined for Windows, Android and alike, as well as diving into the three security layers or areas of security. The first layer investigated was a “physical” device protection which involves the protection of the device and the data on it in case the device was stolen by not allowing anyone to gain access to the device, locking its content. Second protection of the data examined was not allowing applications on the device access to corporate and personal data. Last layer of the protection investigated was in-app information being leaked and otherwise used. Security objectives and mechanisms were also visited in the paper. Literature review on the subject is provided.